Integrasi Konsep Pecahan Melalui Aktualisasi Al-Qur’an dalam Ilmu Faraidh - Khusnul Fadilla; Fitriani (Jurnal Dimensi Matematika, 2023)
The background of this research is to examine the existence of unity and adjustments to the concept of fractions in the science of Faraidh which was developed based on the arguments of the Al-Qur'an. The aim of this research is to integrate the concept of fractions through the actualization of the Al-Qur'an in Faraidh Science. This study used descriptive qualitative method. The type of research is in the form of literature study. The subjects in this research are Fractions and Faraidh Science, while the object in this research is the Al-Qur'an. Data collection in this research was through documentation literature study. The data analysis techniques used in this research are data reduction, data display and conclusions. Based on the research results, it was found that in the Al-Qur'an there are several verses that explain the science of Faraidh, namely in two verses listed in Surah An-Nisa, which are also related to the concept of Fractions. So based on the results of this research, it can be concluded that it is clear that there is unity and adjustment to the concept of fractions in Faraidh Science which is based on the arguments of the Al-Qur'an. Therefore, with this proposition, Faraidh Science can be completed using the Concept of Fractions, this is in accordance with the integration in the Actualization of the Qur'an.